The impacts of private hospital entry on the public market for elective care in England - Elaine Kelly; George Stoye (Institute for Fiscal Studies (IFS), 2020)
This paper examines the impacts of private hospital entry on publicly funded elective care in England. From 2006, private hospitals were encouraged to enter certain publicly funded markets to compete with existing public hospitals and stimulate quality improvements. Studying elective hip replacements, we compare changes in outcomes across areas that were differentially exposed to private hospital entry, instrumenting hospital entry with the location of private hospitals in the pre-reform period. We find private hospital entry led to a 12% increase in the overall number of annual publicly funded admissions, and an 11% reduction in waiting times, but had no effect on the number of admissions at public hospitals or emergency readmissions. Additional publicly funded admissions were not associated with reduced privately funded volumes, and patients became observably healthier on average. These findings indicate the reform successfully increased publicly funded capacity but did little to improve quality at existing public hospitals.
Keywords: I11; I18; L33; 330; Hospital competition; Private provision; Market entry; Independent Sector Providers